Comparative transcriptome analysis reveals cadmium tolerance mechanisms in two Amaranthus varieties - Wang, Taotao; Zhu, Fuqiang; Liu, Ying; Xing, Ningning; Chen, Yuan (Frontiers in Plant Science, 2026)
Cadmium (Cd) pollution poses a significant threat to agricultural safety and ecological health. Understanding plant tolerance mechanisms is crucial for developing solutions. In this study, we investigated the physiological and molecular mechanisms underlying Cd tolerance in two Amaranthus varieties, CZ074 (tolerant) and CZ081 (sensitive). Physiological analysis revealed CZ074 exhibited less severe growth inhibition under Cd stress. Notably, CZ074 exhibited a lower Cd transport coefficient from roots to shoots, which contributes to protecting its aboveground tissues from toxicity. Comparative transcriptome analysis of roots, stems, and leaves identified a significantly larger number of differentially expressed genes (DEGs) in CZ074, suggesting an “active investment” strategy involving comprehensive transcriptional reprogramming. In CZ074 roots, DEGs were markedly enriched in pathways related to phenylpropanoid biosynthesis, cell wall formation (cutin, suberine, and wax), ribosome biogenesis, and plant hormone signal transduction. Key transcription factors (bZIP, NAC, WRKY) and transporter genes (HMA3, NRAMPs, CAXs) were more strongly up-regulated in CZ074 roots, indicating enhanced defense, sequestration, and transport capabilities. In shoots, CZ081 showed more dysregulated gene expression, interpreted as a symptom of severe stress damage rather than an effective defense. We propose that CZ074’s tolerance stems from a coordinated network involving robust root defenses, efficient Cd translocation in stems, all supported by extensive and precise transcriptional regulation. These findings provide valuable candidate genes and insights for phytoremediation and breeding Cd-tolerant crops.